PENGARUH METODE ANDRAGOGI DAN MOTIVASI KERJA TERHADAP KINERJA PENGAJAR - Yulia Safitri (Universitas Bina Sarana Informatika, 2011)
In pursuit of education, especially for adult learners in collages, a teacher needs to create aconducive learning atmosphere. Where learning is directed learners for more effective and active.Learning is an activity that is planned deliberately, sestematis and sestemik in empowering allinteracting components of learning (Teachers, Learners, learning resources, environment,curriculum, clarity of objectives to be achieved) optimally. Learning process by the teacher musthave the motivation to excel in learning and processing of materials provided depending on thecondition of learners, communities of learners, and the material presented and achievementmotivation. Because achievement motivation has a positive influence on the performance ofteachers in the learning process.Keywords: Andragogy, Work Motivation and Performance